Balances in the Migration Theories - Pavel Lisitsyn; Andrey Rezaev; Alexander Stepanov (Journal of Economic Sociology, 2024)
The paper aims to explore how the principles of the neoclassical approach, transformed into meta-theoretical foundations, have changed migration studies. The authors aim to evaluate the extent to which these changes have influenced the theory and practice of migration studies. Focusing its analysis on the works of authors often characterized as representatives of the “economic”/ “neoclassical” approaches, the paper aims to test the thesis that migration theories are characterized by fragmentation and inconsistency. In particular, turning to the analysis of the neoclassical theory, the authors will consider whether the transition from the classical approach in migration studies really laid the foundation for insurmountable contradictions between migration studies and theories of the distant past (late XIX - early XX century), the recent past (mid - late XX century), and the present (XXI century). The current analysis includes the works of A. Lewis, D. Harris and M. Todaro, V. Zelinsky, M. Piore, O. Stark and D. Bloom. The key questions of the analysis will be: Is there a connection between the works of these authors and their predecessors? What contribution have the analyzed studies made to the modern perception of migration? What was the engine of migration studies of this period, often hailed as a breakthrough by most critics (and is it truly a breakthrough)? The authors will be interested in whether something distinguishes the so-called "economic stage of migration research" (the works of representatives of which are presented in the analysis) from other historical stages of migration research? In addition, this analysis offers an assessment of the relevance of the results of migration studies at the end of the XX century for today’s research.